The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1073/pnas.0704879104
|View full text |Cite
|
Sign up to set email alerts
|

Rapid magnetosome formation shown by real-time x-ray magnetic circular dichroism

Abstract: Magnetosomes are magnetite nanoparticles formed by biomineralization within magnetotactic bacteria. Although there have been numerous genetic and proteomic studies of the magnetosomeformation process, there have been only limited and inconclusive studies of mineral-phase evolution during the formation process, and no real-time studies of such processes have yet been performed. Thus, suggested formation mechanisms still need substantiating with data. Here we report the examination of the magnetosome material th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
75
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(85 citation statements)
references
References 29 publications
(31 reference statements)
6
75
0
1
Order By: Relevance
“…However, when cells of Ms. gryphiswaldense were shifted from iron-limited to iron-sufficient conditions, they showed no delay in magnetite production (100), suggesting that no mineral precursors to magnetite are formed during biomineralization or that they are unstable and convert to magnetite extremely quickly. A time period of 15 min is sufficient for full-sized, mature magnetosomes after the addition of iron to iron-limited cells (185). In one study, immature magnetite magnetosome crystals were shown to contain a surface layer of nonmagnetic iron oxide-phase hematite (185).…”
Section: Steps Involved In Magnetosome Chain Formationmentioning
confidence: 99%
“…However, when cells of Ms. gryphiswaldense were shifted from iron-limited to iron-sufficient conditions, they showed no delay in magnetite production (100), suggesting that no mineral precursors to magnetite are formed during biomineralization or that they are unstable and convert to magnetite extremely quickly. A time period of 15 min is sufficient for full-sized, mature magnetosomes after the addition of iron to iron-limited cells (185). In one study, immature magnetite magnetosome crystals were shown to contain a surface layer of nonmagnetic iron oxide-phase hematite (185).…”
Section: Steps Involved In Magnetosome Chain Formationmentioning
confidence: 99%
“…4A). The α-Fe 2 O 3 may be considered as an intermediate phase before Fe 3 O 4 formation, as reported by Staniland et al (11). Based on these observations, we propose that the pathway of magnetosome biomineralization for M. blakemorei strain MV-1 is as follows: i) Iron is taken up from the environment as Fe(II) or Fe(III).…”
Section: Discussionmentioning
confidence: 80%
“…In our previous study, we showed that these immature magnetosomes are nonmagnetic because they have zero XMCD signals (23). In a real-time XMCD study of Magnetospirillum gryphiswaldense strain MSR-1, Staniland et al (11) reported the presence of a surface layer of a nonmagnetic phase, hematite (α-Fe 2 O 3 ), in immature magnetosomes that is rapidly converted to magnetite in a very short time. the magnetosome magnetization.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[4][5][6][7][8] Despite the successful implementation in several branches of technology, the details of iron oxide mineralization both in vivo and in vitro are a subject of ongoing research. [9][10][11][12][13][14][15][16][17][18][19][20][21][22] For example, Mann et al have studied the formation of iron oxides and oxyhydroxides using phospholipid vesicles as a model system. 9 Banfield and coworkers have studied the mineralization of iron oxides on a polymer-based scaffold and have suggested reasons why some microbes release polysaccharide-templated iron oxohydroxides.…”
Section: Introductionmentioning
confidence: 99%